Water-borne Mycobacterium xenopi--a possible cause of pulmonary mycobacteriosis in man - Horák, Z; Poláková, H; Králová, M (Journal of hygiene, epidemiology, microbiology, and immunology, 1986)
In the years 1980-1983 M. xenopi was isolated from the sputum of 37 persons, 30 of them living in the agglomeration of the regional town in the region of Northern Bohemia with 1,175,000 inhabitants. Only 7 of these 30 had manifestation of pulmonary disease. M. xenopi was found repeatedly in the sputum in 5 patients out of 7 affected and in 2 out of 23 persons who showed no signs of a disease. The prevalence was in males between the age of 52-67 years. All of them suffered from other diseases, as chronic bronchitis, TB healed after lobectomy, lung cancer, fibrotic lung lesions, diabetes mellitus, gastric ulcer healed by resection, chronic alcoholism. Investigations were made for detection of the source of infection. Bacteriological examinations of cold and warm tap water in flats of 9 persons with M. xenopi in their sputa were carried out, as well as cold and warm tap water from flats of 2 healthy persons. M. xenopi was found in tap water of 5 persons with M. xenopi in their sputum and in one of the two healthy persons. In the water of one household we found M. kansasii. We came to the conclusion, that transmission carried out in susceptible persons is most probably due to aerosol during washing and showering with water, containing these mycobacteria.
Keywords: Tuberculosis, Pulmonary; lidé středního věku; Water Microbiology; lidé; atypické mykobakteriální infekce; senioři; mužské pohlaví; netuberkulózní mykobakterie; plicní tuberkulóza; mikrobiologie vody; Male; Mycobacterium Infections; Aged; Mycobacterium Infections, Nontuberculous; Nontuberculous Mycobacteria; Middle Aged; mykobakteriózy; Humans